Bacteriophages and Phage-Derived Proteins – Application Approaches - Drulis-Kawa, Z.; Majkowska-Skrobek, G.; Maciejewska, B. (Current Medicinal Chemistry, 2015)
Currently, the bacterial resistance, especially to most commonly used antibiotics has proved to be a severe therapeutic problem. Nosocomial and community-acquired infections are usually caused by multidrug resistant strains. Therefore, we are forced to develop an alternative or supportive treatment for successful cure of life-threatening infections. The idea of using natural bacterial pathogens such as bacteriophages is already well known. Many papers have been published proving the high antibacterial efficacy of lytic phages tested in animal models as well as in the clinic. Researchers have also investigated the application of non-lytic phages and temperate phages, with promising results. Moreover, the development of molecular biology and novel generation methods of sequencing has opened up new possibilities in the design of engineered phages and recombinant phage-derived proteins. Encouraging performances were noted especially for phage enzymes involved in the first step of viral infection responsible for bacterial envelope degradation, named depolymerases. There are at least five major groups of such enzymes – peptidoglycan hydrolases, endosialidases, endorhamnosidases, alginate lyases and hyaluronate lyases – that have application potential. There is also much interest in proteins encoded by lysis cassette genes (holins, endolysins, spanins) responsible for progeny release during the phage lytic cycle. In this review, we discuss several issues of phage and phage-derived protein application approaches in therapy, diagnostics and biotechnology in general.
Keywords: polysaccharide depolymerases